Burden and Timeline of Infectious Diseases in the First Year After Solid Organ Transplantation in the Swiss Transplant Cohort Study. (9th January 2020) - van Delden, Christian; Stampf, Susanne; Hirsch, Hans H; Manuel, Oriol; Meylan, Pascal; Cusini, Alexia; Hirzel, Cédric; Khanna, Nina; Weisser, Maja; Garzoni, Christian; Boggian, Katja; Berger, Christoph; et al.
Abstract: Background: The burden and timeline of posttransplant infections are not comprehensively documented in the current era of immunosuppression and prophylaxis. Methods: In this prospective study nested within the Swiss Transplant Cohort Study (STCS), all clinically relevant infections were identified by transplant–infectious diseases physicians in persons receiving solid organ transplant (SOT) between May 2008 and December 2014 with ≥12 months of follow-up. Results: Among 3541 SOT recipients, 2761 (1612 kidney, 577 liver, 286 lung, 213 heart, and 73 kidney-pancreas) had ≥12 months of follow-up; 1520 patients (55%) suffered 3520 infections during the first year posttransplantation. Burden and timelines of clinically relevant infections differed between transplantations. Bacteria were responsible for 2202 infections (63%) prevailing throughout the year, with a predominance of Enterobacteriaceae (54%) as urinary pathogens in heart, lung, and kidney transplant recipients, and as digestive tract pathogens in liver transplant recipients. Enterococcus spp (20%) occurred as urinary tract pathogens in kidney transplant recipients and as digestive tract pathogens in liver transplant recipients, and Pseudomonas aeruginosa (9%) in lung transplant recipients. Among 1039 viral infections, herpesviruses predominated (51%) in kidney, liver, and heart transplant recipients. Among 263 fungal infections, Candida spp (60%) prevailed as digestive tract pathogens in liver transplant recipients. Opportunistic pathogens, including Aspergillus fumigatus (1.4%) and cytomegalovirus (6%), were rare, scattering over 12 months across all SOT recipients. Conclusions: In the current era of immunosuppression and prophylaxis, SOT recipients experience a high burden of infections throughout the first year posttransplantation, with rare opportunistic pathogens and a predominance of bacteria. Abstract : Data on burden and timeline of infections following solid organ transplantation are currently lacking. This Swiss nationwide cohort study found a high burden of infections throughout the first year posttransplantation, with rare opportunistic pathogens and a predominance of bacteria.